A Trivalent Americium Organic Framework with Decent Structural Stability against Self‐Irradiation. Issue 7 (22nd January 2022) - Zhang, Yugang; Li, Kai; Zhang, Sida; Wang, Xia; Zhang, Hailong; Wang, Yanlong; Wang, Yaxing; Chai, Zhifang; Wang, Shuao
Comprehensive Summary: We reported the synthesis, single crystal structure, and solid‐state UV‐Vis‐NIR spectroscopy of a new transplutonium metal‐organic framework (MOFs), Am(H2 O)[PO[(C6 H4 )COO]3 ], denoted as AmTPO (TPO = tris(4‐carboxylphenyl)‐phosphineoxide). AmTPO forms a three‐dimensional metal−organic framework structure with americium dimers as the secondary building unit. Clear 5f → 5f transitions attributed to trivalent americium was observed in the absorption spectrum of AmTPO ranging from 300 to 1200 nm. Notably, AmTPO can maintain the crystallinity with no observable structural degradation within several months after being synthesized, revealing a long‐term radiation resistance of this structure and the potential application of MOFs as a platform for nuclear waste disposal. Abstract :